The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5007/2175-8069.2021.e76596
|View full text |Cite
|
Sign up to set email alerts
|

Multinacionalidade, ativos intangíveis e agressividade fiscal

Abstract: Atualmente, a agressividade fiscal e a multinacionalidade tem sido temas recorrentes em pesquisas internacionais na área contábil. O objetivo deste estudo é analisar como a agressividade tributária (BTD ou TTVA) é afetada pela multinacionalidade, considerando o nível de ativos intangíveis das empresas listadas na B3. Para isso, foi realizada uma pesquisa quantitativa a partir da análise de regressão, onde testaram-se duas proxies de agressividade fiscal (BTD e TTVA). Os resultados permitem inferir que a presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…According to the regression results, greater intangibles are positively related to greater differences between accounting and tax profits. Other studies such as those of Hasan et al (2017) and Lima et al (2021) had also found the same evidence. Thus, according to Tang and Firth (2011), intangible assets, as well as tangible ones, also generate amortizations.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…According to the regression results, greater intangibles are positively related to greater differences between accounting and tax profits. Other studies such as those of Hasan et al (2017) and Lima et al (2021) had also found the same evidence. Thus, according to Tang and Firth (2011), intangible assets, as well as tangible ones, also generate amortizations.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 64%
“…Thus, according to Tang and Firth (2011), intangible assets, as well as tangible ones, also generate amortizations. Thus, the positive relationship between non-compliance and these assets, according to Hasan et al (2017) and Lima et al (2021) is explained by the different recognitions in accounting and tax rules and also due to the difficulties to verify their values and the tax benefits generated by the amortizations (Silva, 2016).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%